Rapid identification of RNA‐interference‐based resistance to Bean golden mosaic virus in transgenic common beans via loop‐mediated isothermal amplification. Issue 6 (22nd September 2020) - Teixeira, Nara Cristina; Wendland, Adriane; Oliveira, Maythsulene Inácio de Souza; Brandão, Livia Teixeira Duarte; de Souza, Thiago Lívio Pessoa Oliveira; de Faria, Josias Correa; Del Peloso, Maria José; Cortes, Marcio Vinicius de Carvalho Barros
Abstract: A molecular tool was adapted for practical identification of the world's first transgenic event (Embrapa 5.1) in common bean ( Phaseolus vulgaris L.). Based on the technology of RNA interference and on the transformation of plants via the Biobalistic method, a transgenic bean was created with effective resistance to Bean golden mosaic virus, its principal virus. To support the monitoring of this technology, the development of new cultivars, and the process of producing, benefiting, and distributing of seeds and grains, a molecular detection tool based on loop‐mediated isothermal amplification (LAMP) was developed. This tool can facilitating diagnosis, making it fast, specific, low‐cost, and easily executed. Based on the gene Ahas (GenBank M88686) of the Embrapa 5.1 event, sets of initiators were planned (forward outer primer–backward outer primer and forward inner primer–backward inner primer) that are characteristic of the LAMP method. These were evaluated for their sensitivity and specificity in detecting their target. The LAMP method allows direct visual interpretation. The Neutral Red (NR) pH indicator was adopted to facilitate molecular diagnosis in moderately well equipped environments, thus reducing the risk of contamination and the need for skilled labor. This agility in diagnosis occurs because several phases commonly used in molecular techniques, such as polymerase chain reaction, can be excluded. The LAMP method, combined with a rapid DNA extraction method (modified NaOH) and the addition of NR, provides technological support for addressing issues of biosafety, traceability, and identification of the Embrapa 5.1 event in beans in the field and in industry.